Filantropi Sosial dalam Program Respon Bencana Sekolah Relawan: Studi Netnografi tentang Solidaritas Netizen - Andria, Yoga Riski; Romadi, Pipir (Islamic Management and Empowerment Journal, 2026)
Social philanthropy is one of the approaches used to address the impacts of disasters in Indonesia. This study aims to analyze the contribution of Sekolah Relawan in preparing volunteers and to examine netizens’ responses to its Disaster Response program. The research employed a qualitative method with a netnographic approach. Data were collected from netizens’ comments on Sekolah Relawan’s TikTok and Instagram accounts and analyzed using thematic analysis. The findings show that Sekolah Relawan strengthens volunteer capacity through Volunteer Orientation, Volunteer Upgrading Skill, and Disaster Leadership Training programs. Netizens’ responses to the Disaster Response program were dominated by expressions of social solidarity, empathy, prayers, moral support, and willingness to donate and participate in volunteer activities. These findings indicate that social media can serve as a platform for encouraging public participation and strengthening social solidarity in disaster response efforts.